Optical spectroscopy and microscopy of radiationinduced light-emitting point defects in lithium fluoride crystals and films - Montereali, R.M.; Bonfigli, F.; Menchini, F.; Vincenti, M.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
Broad-band light-emitting radiation-induced F2 and F3 + electronic point defects, stable and laser-active at room temperature in lithium fluoride crystals and films, find applications in dosimeters, tuneable color-center lasers, broad-band miniaturized light sources and in novel radiation imaging detectors. A brief review of their photoemission properties is presented, and their peculiarities at liquid nitrogen temperature are discussed. A fewexperimental results about optical spectroscopy and fluorescence microscopy of these radiation-induced point defects in LiF crystals and thin films are presented to obtain information about the coloration curves, the point defects formation efficiency, the effects of the photo-bleaching processes, and so on. The control of local formation, stabilization and transformation of radiation-induced light-emitting defect centers is crucial for the developmentof optical active micro-components and nanostructures. Some of the advantages of low temperature measurements for novel confocal laser scanning fluorescence microscopy techniques, widely used for the spatial mapping of these point defects thorough the optical reading of their visible photoluminescence, are highlighted.